Early prediction of the success of methotrexate treatment success by 24–hour pretreatment increment in HCG and day 1–4 change in HCG. Issue 1 (July 2019) - Levin, Gabriel; Dior, Uri; Shushan, Asher; Gilad, Ronit; Benshushan, Avi; Rottenstreich, Amihai
Abstract: Research question: Several studies have tried to identify early markers of treatment outcome after methotrexate (MTX) treatment for ectopic pregnancy, including pretreatment and day 4 human chorionic gonadotrophin (HCG) concentrations and their corresponding changes, and the increment in HCG during the initial 24 h after treatment. There have, however, been conflicting results. This study aimed to re-evaluate the role of these markers in the earlier identification of treatment success in a large cohort of women. Design: This was a retrospective cohort study including women diagnosed with an ectopic pregnancy and treated with a regimen of a single dose of MTX. A comparison of maternal and gestation characteristics was made between groups in whom treatment was successful or failed. Results: A total of 292 women treated with single-dose intramuscular MTX for ectopic pregnancy were included in this study. In the overall cohort, the treatment success rate with a single dose of MTX was 62.7% (183/292). Only two independent determinants were significantly associated with treatment success: the initial 24-h percentage increase in HCG (adjusted odds ratio [OR] 1.82, 95% confidence interval [CI] 1.26–2.63; P < 0.001) and the percentage change in HCG from day 1 to day 4 (adjusted OR 1.12, 95% CI 1.04–1.21; P < 0.001). The optimal cut-off points for prediction of treatment success were an increment of less than 17% in the 24 h before treatment and a decrease of more than 22% between the day 1 and day 4 HCG concentrations. Conclusions: A small increase in HCG concentration 24 h before treatment with MTX, alongside a decline in HCG concentration from day 1 to day 4, may predict the success of medical treatment for an ectopic pregnancy.